Intelligent Transportation Systems - Cenek, Petr (Communications - Scientific letters of the University of Zilina, 2003)
Intelligent transportation system (ITS) stands for a transportation system with improved quality of control using an added “intelligence”. Improved control can be attained by optimisation methods, by simualtions, interactive methods or artificial intelligence. Anyhow, a suitable model of the system, correct input data, optimisation routines and user-friendly environment for data input and output are typical parts of such a system. Basic parts of a transportation system, transportation processes and their models, optimisation methods and problems of implementation of an ITS are discussed in the paper in more detail.